Joint Responsibility Shared Rewards : The Managing Director's Global Policy Agenda. (Policy Papers; Policy Paper ;, 2019)
International cooperation, economic and financial integration, and technological progress have delivered enormous benefits across the globe during the past decades. Yet, in many countries, these benefits have not been shared adequately to prevent eroding trust in institutions and weakening support for the global system that has made these gains possible.